Inductive Risk, Science, and Values: A Reply to MacGillivray. Issue 4 (23rd December 2019) - Hicks, Daniel J.; Magnus, P. D.; Wright, Jessey
Abstract: The argument from inductive risk (AIR) is perhaps the most common argument against the value‐free ideal of science. Brian MacGillivray rejects the AIR (at least as it would apply to risk assessment) and embraces the value‐free ideal. We clarify the issues at stake and argue that MacGillivray's criticisms, although effective against some formulations of the AIR, fail to overcome the essential concerns that motivate the AIR. There are inevitable trade‐offs in scientific enquiry that cannot be resolved with any formal methods or general rules. Choices must be made, and values will be involved. It is best to recognize this explicitly. Even so, there is more work to be done developing methods and institutional support for these choices.